Individual Specialization in a Generalist Apex Predator: The Leopard Seal - Emily S. Sperou; Douglas J. Krause; Renato Borras‐Chavez; Patrick Charapata; Daniel P. Costa; Daniel E. Crocker; Kerri J. Smith; Bradley Thompson; Azana Best; Jaelyn Anderson; Michael E. Goebel; Carolina A. Bonin; et al. (Ecology and Evolution)
ABSTRACT Apex predators are typically considered dietary generalists, which often masks individual variability. However, individual specialization—consistent differences among individuals in resource use or ecological role—is common in apex predators. In some species, only a few specialized individuals can significantly impact prey populations. Leopard seals (Hydrurga leptonyx) are apex predators important to the structure and function of the Southern Ocean ecosystem. Though broadly described as generalists, little is known about their trophic ecology at the population or individual level. We analyzed δ13C and δ15N profiles in whiskers (n = 46) from 34 leopard seals in the Western Antarctic Peninsula to assess trophic variation. We also evaluated individual consistency across years using repeat samples from 7 seals over 2–10 years. We compared population and individual isotopic niche space and explored drivers of intraspecific variation in leopard seal trophic ecology. We find that leopard seals have a broad trophic niche (range: 6.96%–15.21‰) and are generalists at the population level. However, most individuals are specialists (59% for δ15N and δ13C), with only a few generalists (13% for δ15N, 6% for δ13C). Individuals also specialize at different trophic levels. Most variation in trophic ecology is driven by individual specialization, but sex and mass also contribute. We also find that some seals specialize over time, consistently foraging at the same trophic level, while others switch within and between years. This suggests some seals may disproportionately impact prey, especially when specialists consistently target specific species. Long‐term specialization by a few leopard seals likely contributed to the decline of the local Antarctic fur seal population. Our findings show the importance of examining individual specialization in leopard seals across their range to understand their impact on other prey populations. This approach should be applied to other apex predator populations, as a few specialists can significantly impact ecosystems.